Microinteractions - Saffer, Dan, ....- (Beijing : O'Reilly, 2013)
It's the little things that turn a good digital product into a great one. With this practical book, you'll learn how to design effective microinteractions: the small details that exist inside and around features. How can users change a setting? How do they turn on mute, or know they have a new email message? Through vivid, real-world examples from today's devices and applications, author Dan Saffer walks you through a microinteraction's essential parts, then shows you how to use them in a mobile app, a web widget, and an appliance. You'll quickly discover how microinteractions can change a product from one that's tolerated into one that's treasured.
Includes index.
Keywords: Application software -- Development; Human-computer interaction; User interfaces (Computer systems).; System design